Plastome phylogenomics of Micromeles (Rosaceae) - Ma, Jian-Hui; Chen, Xin; Hou, Wen-Xiang; Geng, Li-Yang; Tang, Chen-Qian (Phytotaxa, 2023)
Micromeles has been the focus of discussion concerning its relationship with other genera of Sorbus s.l., Maleae, Rosaceae. With the aim to shed light on its circumscription, phylogenetic relationships were investigated using plastomes. The 14 newly sequenced Micromeles plastomes range in size from 159,753 to 160,512 bp, contain 113 unique genes arranged in the same order, including 79 protein-coding, 30 tRNA, and 4 rRNA genes. Phylogenetic analyses using ML/BI indicated that Micromeles and the other five genera traditionally segregated from Sorbus s.l., Aria, Chamaemespilus, Cormus, Sorbus s.s. and Torminalis, are monophyletic. However, Micromeles and the five genera recently delimited by Rushforth in Sorbus s.l., Alniaria, Dunnaria, Griffitharia, Thomsonaria and Wilsonaria, are paraphyletic. Micromeles is here supported to include all the Asian simple-leaved members of Sorbus s.l.